ОБЩЕДОСТУПНЫЕ БИБЛИОТЕКИ РЕСПУБЛИКИ БАШКОРТОСТАН И УДОВЛЕТВОРЕНИЕ ЭТНОКУЛЬТУРНЫХ ПОТРЕБНОСТЕЙ НАСЕЛЕНИЯ (ПО ИТОГАМ ПРОВЕДЕННОГО ИССЛЕДОВАНИЯ) (Библиосфера, 2012)
The results of the sociological research on the role and place of a public library as a social and cultural institution in meeting the ethno-cultural needs of population in Bashkortostan and forming the national-cultural identity of a personality are shown.